Feminization Poverty in Tulusbesar Village, Tumpang Sub-district, Malang Regency - Irma Fitriana Ulfah; Laode Machdani Afala; Marini Elshabrina (Wacana Journal of Social and Humanity Studies, 2019)
This paper explains about the poverty experienced by women who become the backbone of the family. They are known as the Head of Female Household (KRTP). The research is located in Tulusbesar Village, Tumpang Sub-district, Malang Regency. KRTP is caused by husband died, divorced, husband sick, abandoned husband, and husband with disable. The feminization of poverty is seen from how the source of income KRTP and how the allowance system or social aids have not overcome the KRTP’s poverty yet. In this paper, the source of income of KRTP is viewed from income public transfers and income private transfers. The income private transfers are obtained from ex-husband or family, while the income public transfers are non-occupational income, derived from the government consisting of Jalin Matra, BLT, BPJS, and PKH programs as social aids. All KRTPs in Tulusbesar Village have received social aid, but the four existing social aids have not been accepted by the KRTP overall. In private transfer, based on the results of the study there are 20 KRTPs who have received help from their families and 36 KRTPs do not get help from their families. The life of the KRTP in Tulusbesar village after receiving social aids is still experiencing the vulnerability of poverty, because the social aids received are temporary and only lasts short term. Thus, it makes KRTP more vulnerable to poverty.